PENGARUH PENDEKATAN RME TERHADAP KEMAMPUAN PEMECAHAN MASALAH MATEMATIS PESERTA DIDIK KELAS VIII DI SMPN 1 GUNUNG TALANG - Azizah, Rahmi; Elniati, Sri (Jurnal Edukasi dan Penelitian Matematika, 2024)
Students should learn mathematical problem-solving. This is still lacking in classrooms. For this, Realistic Mathematics Education (RME) was used. This study will examine if the approach used to teach VIII graders at SMPN 1 Gunung Talang is better than the standard approach. This pseudo-experimental study uses Nonequivalent Posttest-Only Control Group Design. This study examined SMP 1 Gunung Talang VIII graders' demographics. Basic random sampling picked class VIII-1 as the experimental group and class VIII-2 as the control group. Math problem-solving ability test data analysis yielded a 0.00 P-value. At a significance threshold (α) of 0.05, the null hypothesis (H0) is rejected as the P-value is below α. RME pupils outperform Conventional students in class VIII SMPN 1 Gunung Talang.Keywords– Mathematical Problem Solving Abilities, RME